ASSESSMENT OF VEHICLE EFFECTIVE MODERNIZATION TAKING INTO ACCOUNT THE LIFE CYCLE COST, TECHNICAL AND ENVIRONMENTAL PARAMETERS - Volodarets, M.; Володарець, М. В.; Володарец, Н. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The article deals with the features for determination of the efficiency of vehicle modernization compared to the base one. They propose the model for determining the efficiency of vehicle modernization compared with the base one. The model takes into account technical, economic and environmental parameters of the vehicle.
ОЦІНКА ЕФЕКТИВНОСТІ МОДЕРНІЗАЦІЇ ТРАНСПОРТНОГО ЗАСОБУ З УРАХУВАННЯМ ВАРТОСТІ ЖИТТЄВОГО ЦИКЛУ, ТЕХНІЧНИХ І ЕКОЛОГІЧНИХ ПАРАМЕТРІВ
ОЦЕНКА ЭФФЕКТИВНОСТИ МОДЕРНИЗАЦИИ ТРАНСПОРТНОГО СРЕДСТВА С УЧЕТОМ СТОИМОСТИ ЖИЗНЕННОГО ЦИКЛА, ТЕХНИЧЕСКИХ И ЭКОЛОГИЧЕСКИХ ПАРАМЕТРОВ
Keywords: vehicle efficiency; life cycle; life cycle cost; technical level coefficient; environmental parameters; транспортний засіб; ефективність; життєвий цикл; вартість життєвого циклу; коефіцієнт технічного рівня; екологічні показники; транспортное средство; эффективность; жизненный цикл; стоимость жизненного цикла; коэффициент технического уровня; экологические показатели; 629+656.1:656.2